Sustainable cooling in a warming world: technologies, cultures, and circularity - Khosla, Radhika; Renaldi, Renaldi; Mazzone, Antonella; McElroy, Caitlin; Palafox-Alcantar, Giovani (Annual Reviews, 2022)
Cooling is fundamental to quality of life in a warming world, but its growth trajectory is leading to a substantial increase in energy use and greenhouse gas emissions. The world is currently locked into vapor-compression air conditioning as the aspirational means of staying cool, yet billions of people cannot access or afford this technology. Non–vapor compression technologies exist but have low Technological Readiness Levels. Important alternatives are passive cooling measures that reduce mechanical cooling requirements and often have long histories of local use. Equally, behavioral and cultural approaches to cooling play a vital role. Although policies for a circular economy for cooling, such as production and waste, recovery of refrigerants, and disposal of appliances, are in development, more efforts are needed across the cooling life cycle. This article discusses the knowledge base for sustainable cooling in the built environment and its significant, interconnected, and coordinated technical, social, economic, and policy approaches.
Keywords: cooling; energy; air conditioning; passive cooling; circular economy; climate change; behavior and culture